2018
DOI: 10.1002/gps.4977
|View full text |Cite
|
Sign up to set email alerts
|

Compassion focused therapy for people with dementia: A feasibility study

Abstract: Compassion focused therapy can be adapted to be delivered to people with dementia and low mood, anxiety, or other distress. The intervention may improve self-compassion, mood, and anxiety. A larger pilot trial with a comparator group and follow-up is needed to evaluate the intervention's effectiveness for people with dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…The CFT group showed more improvements than the TAU group in psychopathology, fear of selfcompassion, and social safety. In addition, groupbased CFT has been applied in observational studies without control groups and found to benefit individuals struggling with personality disorders (32), dementia (33,34), eating disorders (35), and complex MH problems (5,36).…”
Section: Introductionmentioning
confidence: 99%
“…The CFT group showed more improvements than the TAU group in psychopathology, fear of selfcompassion, and social safety. In addition, groupbased CFT has been applied in observational studies without control groups and found to benefit individuals struggling with personality disorders (32), dementia (33,34), eating disorders (35), and complex MH problems (5,36).…”
Section: Introductionmentioning
confidence: 99%
“…The results of non-randomized clinical trials have found that group-based CFT can benefit individuals who struggle with personality disorders (Lucre & Corten, 2013), dementia (Collins, Gilligan, & Poz, 2018;Craig, Hiskey, Royan, Poz, & Spector, 2018), eating disorders (Gale, Gilbert, Read, & Goss, 2014), and complex MH problems (Gilbert & Procter, 2006;Judge, Cleghorn, McEwan, & Gilbert, 2012). However, qualitative research studies of participants' perspectives and experiences of group-based CFT interventions are scarce.…”
mentioning
confidence: 99%
“…Other client groups who experience challenges with traditional talking therapies may also benefit from such a creative approach to CFT. This includes but is not limited to CFT for people with intellectual and developmental disabilities (Clapton, Williams, Griffith, & Jones, 2018; Cowles, Randle‐Phillips, & Medley, 2018), acquired brain injury (Ashworth, Clarke, Jones, Jennings, & Longworth, 2015), and dementia (Craig, Hiskey, Royan, Poz, & Spector, 2018). The Compassionate Kitbag can also be used as an adjunct to stabilization, resourcing and reprocessing work in trauma‐focused approaches such as EMDR for people with PTSD and CPTSD (Beaumont & Martin, 2013; Kennedy, 2014; Whalley & Lee, 2019).…”
Section: Concluding Comments and Call For Further Researchmentioning
confidence: 99%